Epidemiology, genetics and treatments for myopia - Yu, Lei (International Journal of Ophthalmology Press, 2011)
Myopia is a significant public health problem and its prevalence is increasing over time and genetic factors in disease development are important. The prevalence and incidence of myopia within sampled population often varies with age, country, sex, race, ethnicity, occupation, environment, and other factors. Myopia growth is under a combination of genes and their products in time and space to complete the coordination role of the guidance. Myopia-related genes include about 70 genetic loci to which primary myopias have been mapped, although the number is constantly increasing and depends to some extent on definition. Of these, several are associated with additional abnormalities, mostly as part of developmental syndromes. These tend to result from mutations in genes encoding transcriptional activators, and most of these have been identified by sequencing candidate genes in patients with developmental anomalies. Currently, COL1A1 (collagen alpha-1 chain of type I), COL2A1 (collagen alpha-1 chain of type II), ACTC1 (actin, alpha, cardiac muscle 1), PAX6 (paired box gene 6) and NIPBL (nipped-B homolog), and so on have been mapped. Myopia is most commonly treated with spectacles or glasses. The most common surgical procedure performed to correct myopia is laser in situ keratomileusis (LASIK). This review of the recent advances on epidemiology, genetic locations and treatments of myopia are summarized.